Latent structure of situational efficiency parameters at Croatian top basketball players - Sindik, J.; Jukic, I.; Adzija, M. (SportLogia, 2012)
The aim of this study was to determine the structure of dimensions that are based on different parameters of the standard situational efficiency of top Croatian players. The insight into the structure and relationships of the latent dimensions of situational success in basketball could contribute to better understand the overall effectiveness of situational players. We analyzed twelve standard and seven derived parameters of situational efficiency in a intentional sample of players in nine senior basketball teams from the A-1 Croatian Basketball League Championship in 2006/2007. Principal components analysis of the standard situational efficiency parameters obtained the existence of three main components, which all together explain over 76% of the total variance of the space of standard parameters of situational efficiency. Univariate correlations and results of principal components analysis showed that the most standard and most of the derived parameters of situational efficiency are statistically significantly correlated.